2015
DOI: 10.1371/journal.pone.0133392
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1 Phosphate at the Blood Brain Barrier: Can the Modulation of S1P Receptor 1 Influence the Response of Endothelial Cells and Astrocytes to Inflammatory Stimuli?

Abstract: The ability of the Blood Brain Barrier (BBB) to maintain proper barrier functions, keeping an optimal environment for central nervous system (CNS) activity and regulating leukocytes’ access, can be affected in CNS diseases. Endothelial cells and astrocytes are the principal BBB cellular constituents and their interaction is essential to maintain its function. Both endothelial cells and astrocytes express the receptors for the bioactive sphingolipid S1P. Fingolimod, an immune modulatory drug whose structure is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 65 publications
0
55
0
Order By: Relevance
“…24 But fingolimod does cross the blood-brain barrier (BBB) and acts on sphingosine-1-phosphate receptor 1, 3, and 5 in the CNS and may potentially influence the integrity of the BBB, neurons, and oligodendrocytes. 25 However, a few in vitro and in vivo studies show that the influence from fingolimod medication directly on cells in the CNS is limited. 26 The role of fingolimod in myelin repair is still controversial but in cuprizone and lysolecithin (LPC) demyelination animal models, fingolimod did not promote remyelination.…”
Section: Discussionmentioning
confidence: 99%
“…24 But fingolimod does cross the blood-brain barrier (BBB) and acts on sphingosine-1-phosphate receptor 1, 3, and 5 in the CNS and may potentially influence the integrity of the BBB, neurons, and oligodendrocytes. 25 However, a few in vitro and in vivo studies show that the influence from fingolimod medication directly on cells in the CNS is limited. 26 The role of fingolimod in myelin repair is still controversial but in cuprizone and lysolecithin (LPC) demyelination animal models, fingolimod did not promote remyelination.…”
Section: Discussionmentioning
confidence: 99%
“…As for endothelial cells, our previous study revealed direct BBB‐modulating effects which included the enhancement of the barrier properties of the BBB by upregulation of claudin‐5 expression and inhibition of the increase in VCAM‐1 levels in BMECs induced by MS sera (Nishihara et al., 2015). Other laboratories have also shown that S1P receptor signaling reduces the cell death resulting from inflammatory cytokines (Spampinato et al., 2015). These reports indicated that fingolimod directly affects endothelial cells which might contribute to its efficacy in the treatment of MS.…”
Section: Discussionmentioning
confidence: 99%
“…BBB is regulated by S1PRs signaling, 64 and FTY720 can directly repair BBB under inflammatory conditions by up-regulation of claudin-5 and down-regulation of VCAM-1 in brain microvascular endothelial cells through modulation of S1P1. 65 However, it remains unknown whether FTY720 can protect BRB. We show that FTY720 can reduce retinal microvascular permeability and preserve BRB integrity.…”
Section: Discussionmentioning
confidence: 99%